Effectiveness of functional magnetic resonance imaging for early identification of chronic kidney disease: A systematic review and network meta-analysis. Issue 160 (March 2023) - Zhou, Huan; Si, Yi; Sun, Jiantong; Deng, Jiaxin; Yang, Ling; Tang, Yi; Qin, Wei
Highlights: fMRI has potential to identify patients with early and different CKD stages. DTI, IVIM, and BOLD could differentiate early CKD patients from the healthy controls. DWI showed superiority in distinguishing different CKD stages. Abstract: Purpose: The commonly used clinical indicators are not sensitive enough on detecting early chronic kidney disease (CKD), whether functional magnetic resonance imaging (fMRI) can be regarded as a new noninvasive method to identify early stages of CKD and even different stages remains unknown. We performed a network meta -analysis to explore the question. Methods: Five databases were searched to identify eligible articles from 2000 to 2022. The outcome indicators were imaging biomarkers of fMRI techniques, including apparent diffusion coefficient (ADC) by diffusion-weighted imaging (DWI), fractional anisotropy (FA) by diffusion tensor imaging (DTI), diffusion coefficient (D), pseudodiffusion coefficient (D*), and perfusion fraction (f) by intravoxel incoherent motion imaging (IVIM), and apparent relaxation rate (R2*) by blood oxygen level-dependent (BOLD). Results: A total of 21 articles with 1472 patients were included for analysis. Cortical FA, f, and R2* values in CKD stages 1–2 were found statistically different with healthy controls (mean difference (MD), −0.03, 95% confidence interval (CI) −0.05, −0.01; MD, −0.04, 95% CI −0.06, −0.02; MD, 2.22, 95% CI 0.87, 3.57, respectively), and cortical ADC values were significantly different among different CKD stages (stages 3 and 1–2: MD, −0.15, 95% CI −0.23, −0.06; stages 4–5 and 3: MD −0.27, 95% CI −0.39, −0.14). Conclusion: The results indicated fMRI techniques had great efficacy in assessing early stages and different stages of CKD, among which DTI, IVIM, and BOLD exerted great superiority in differentiating early CKD patients from the general population, while DWI showed the advantage in distinguishing different CKD stages.